The IBM i programmer's guide to PHP - Olen, Jeff.; Schroeder, Kevin; Safari eBooks (Lewisville, Tex. : MC Press Online, 2009)
"This is the first book to comprehensively address PHP and how it can--and should--be deployed on the IBM i. With this IBM i-specific point of view, the authors examine how to transfer skills from a green screen environment to the Web, become intimately familiar with PHP's commonly used features, and help start down the road of highly interactive Web-based application development"--Resource description page.
Description based on print version record.
Includes index.
Keywords: PHP (Computer program language); Web-based user interfaces; i5/OS.; MySQL (Electronic resource); Electronic books